(untitled) (Raparin Journal of Humanities (RJH), 2023)
Abstract Research Aims:- The researcher pursues the following aims in this research:- 1-The level of risk-taking behavior among university students for the sample. 2- The level of self-confidence among university students for the sample. 3- The level of risk-taking behavior and self-confidence according to the variable (gender - economic status). 4- The relationship between risk-taking behavior and self-confidence in the sample. The current research community consists of Salah El-Din University students for the academic year (2021-2022)، for the sake of the research sample، the two researchers chose a random sample of (250) students for their research. To measure the two variables، the researchers followed the following procedures، to measure the variable (risk-taking behavior)، the researchers found it better to build a measure of risk behavior because there is no measure of risk behavior، and the scale consisted of (39) items، and they extracted the apparent validity of the scale and did not delete any item from the scale، and they extracted the power Discriminatory paragraphs did not delete any paragraph also. The two researchers relied on the self-confidence scale prepared by (Al-Badrany, The scale consists of (40) items، and they extracted the apparent validity of the scale and did not delete any item from the scale. The two researchers relied on the re-test method to calculate the stability of the two scales، risk behavior and self-confidence، as it reached in risk behavior (0.91) and in self-confidence (0.77). The two researchers reached the following results:- • The results of this research indicate that the students’ risk-taking behavior is high and their self-confidence is good. • The gender variable and the economic status variable are not among the variables affecting risk-taking behavior and self-confidence. • There is a positive relationship between risk-taking behavior and students’ self-confidence. The two researchers presented a set of recommendations and suggestions in their research.